The dynamic changes of glycogen molecular structure in Escherichia coli BL21(DE3). (1st May 2021) - Wang, Mengmeng; Liu, Qinghua; Li, Fen; Tang, Jiawei; Xiong, Xuesong; Yang, Yingying; Ju, Pei; Wang, Ziyi; Gilbert, Robert G.; Wang, Liang
Highlights: Liver glycogen can have small β particles bonded into composite α particles. In healthy mice, α particles in liver glycogen are stable in dimethyl sulfoxide. Identification of glycogen synthesis and degradation periods in E. coli . Bacterial glycogen is fragile at synthesis stage and stable at degradation stage. Glycogen metabolic enzymes are responsible for bacterial glycogen fragility. Abstract: Diurnal alteration of glycogen molecular structure has been identified in healthy mice. Recently, both fragile (disintegration in dimethyl sulfoxide) and stable (not disintegrating in DMSO) glycogen particles were found in Escherichia coli . However, how glycogen structure changes dynamically in E. coli is not clear. The question examined here is whether fragile, stable glycogen α particles occur in bacteria, following a similar pattern as in mice. In this study, we examine the dynamic changes of glycogen molecular structure over 24-h in E. coli BL21(DE3), using transmission electron microscopy, size exclusion chromatography and fluorophore-assisted carbohydrate electrophoresis at representative time points. It was found that glycogen structure was mainly fragile at the synthesis stage and largely stable during the degradation stage. qRT-PCR results indicated that balance of anabolic and catabolic gene expression levels in glycogen metabolism could be a key factor affecting the fragility of glycogen α particles in bacteria.